2014
DOI: 10.5455/bcp.20140702010106
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Risks due to Methylphenidate in Six Months of Treatment in Children with Attention Deficit and Hyperactivity Disorder

Abstract: ÖZET:Dikkat eksikliği hiperaktivite bozukluğu olan çocuklarda metilfenidat tedavisinin altıncı ayında kardiyovasküler risklerin değerlendirilmesi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…16,17 For example, the development of tic disorder, elongated QT durations or the onset of depression, psychosis and/or mania were identified in some MPH-treated individuals. 11,18 Furthermore, a recent comprehensive meta-analysis including 185 studies of MPH use for ADHD treatment reported a high frequency of non-serious adverse events associated with treatment, including for example, insomnia and loss of appetite. 19 Currently, no clinical guidelines exist to address these issues with a personalized approach for individualized medication.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 For example, the development of tic disorder, elongated QT durations or the onset of depression, psychosis and/or mania were identified in some MPH-treated individuals. 11,18 Furthermore, a recent comprehensive meta-analysis including 185 studies of MPH use for ADHD treatment reported a high frequency of non-serious adverse events associated with treatment, including for example, insomnia and loss of appetite. 19 Currently, no clinical guidelines exist to address these issues with a personalized approach for individualized medication.…”
Section: Introductionmentioning
confidence: 99%